Predicting adolescent aggressive behavior from community violence exposure, deviant peer affiliation and school engagement: A one-year longitudinal study. (April 2020) - Lin, Shuang; Yu, Chengfu; Chen, Jun; Zhang, Wei; Cao, Lei; Liu, Lihong
Highlights: DPA mediated the link between CVE and AB. SE and DPA sequentially mediated the relationship between CVE and AB. The pathway from DPA to subsequent SE was not evident in the final model. Abstract: Community violence exposure (CVE) functions as a risk factor for adolescent aggressive behavior, but the mediating mechanisms underlying this relationship are not well understood. This longitudinal study examined the mediating effects of school engagement and deviant peer affiliation on the relationship between CVE and aggressive behavior in a sample of 732 Chinese adolescents. Structural equation modeling indicated that CVE in the fall of seventh grade diminished school engagement in the spring of seventh grade, which enhanced deviant peer affiliation in the fall of eighth grade leading to increased aggressive behavior in the fall of eighth grade. CVE in the fall of seventh grade directly increased deviant peer affiliation in the spring of seventh grade, which increased aggressive behavior in the fall of eighth grade. The non-significant pathway from deviant peer affiliation to subsequent school engagement suggests that deviant peer affiliation may have a proximal association with adolescent aggressive behavior. Understanding the mechanism of association between CVE and aggression has implications for preventing adolescent aggressive behavior.